The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10856-009-3854-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel nano drug delivery system based on tigecycline-loaded calciumphosphate coated with poly-dl-lactide-co-glycolide

Abstract: The purpose of the study presented in this paper has been to examine the possibility of the synthesis of a new nanoparticulate system for controlled and systemic drug delivery with double effect. In the first step, a drug is released from bioresorbable polymer; in the second stage, after resorption of the polymer, non-bioresorbable calcium phosphate remains the chief part of the particle and takes the role of a filler, filling a bone defect. The obtained tigecycline-loaded calcium-phosphate(CP)/poly(DL-lactide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
0
31
0
6
Order By: Relevance
“…The average size was from 65-95 nm. This composited nanoparticles proved to be an adequate system for local and controlled drug release [50]. Another group of novel composite nanoparticles combining glycidyl methacrylate derivatised dextrans with gelatine was reported.…”
Section: Composite Nanoparticle-based Systemmentioning
confidence: 94%
“…The average size was from 65-95 nm. This composited nanoparticles proved to be an adequate system for local and controlled drug release [50]. Another group of novel composite nanoparticles combining glycidyl methacrylate derivatised dextrans with gelatine was reported.…”
Section: Composite Nanoparticle-based Systemmentioning
confidence: 94%
“…Upravo ovakav koncept je primenjen u dizajniranju nHAP-a za lokalnu dostavu tigeciklina a u cilju lečenja osteomijelitisa [63,64]. Kompozitni biomaterijal na bazi HAp/PLLA [65], sa visoko kristalnom HAp fazom, je sintetizovan u dva koraka.…”
Section: Sinteza I Dizajniranje Multifunkci-unclassified
“…66 Apart from PLGA-related nanomaterials, other targeted delivery systems for bone diseases were reported. For example, Ignjatović et al 67 reported a double delivery system where a new nanoparticulate system for controlled and systemic drug delivery with double effect was reported. In their design, the drug is released from the bioresorbable polymer first; then, after resorption of the polymer, nonbioresorbable calcium phosphate remains the chief part of the particle and takes the role of a filler, filling a bone defect.…”
Section: Infection and Inflammatory Bone Diseasesmentioning
confidence: 99%